2012
DOI: 10.1590/s1516-35982012000300042
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of a bioeconomic efficiency index for beef cattle production in Rio Grande do Sul, Brazil

Abstract: An index was developed to estimate the bioeconomic efficiency of production systems, identifying alternative scenarios that could improve their efficiency, and building isoefficiency relations in beef cattle production systems in Rio Grande do Sul. The concept of return on investment was used to develop the indicator. Scenarios regarded as efficient showed values higher than 3. The bioeconomic efficiency index for beef cattle production in the theoretical reference scenario was considered inefficient. At least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 8 publications
1
16
0
2
Order By: Relevance
“…Among genetic groups, ½ Simmental + ½ Nellore heifers showed high probability of pregnancy with less weight. This fact may be due to the younger age at the beginning of reproductive life in this genetic group, as well as the individual heterosis for this variable (Lemos et al, 1992).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Among genetic groups, ½ Simmental + ½ Nellore heifers showed high probability of pregnancy with less weight. This fact may be due to the younger age at the beginning of reproductive life in this genetic group, as well as the individual heterosis for this variable (Lemos et al, 1992).…”
Section: Resultsmentioning
confidence: 97%
“…Increasing birth rate by one percentage point and reducing ages of mating and slaughter by one year resulted in average increases in production per hectare of 0.84%, 9.19% and 8.11% and in the outcome rates of 0.88%, 8.81% and 19.7%, respectively (Lampert et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The subfactor feed supplementation refers to the use of feed supplements and to associate characteristics, such as nutritional value, cattle management, and expected weight gain. Several authors have reported that the efficiency of feed supplementation depends on cost monitoring and on the forecast of financial results (Pilau et al, 2003;Figueiredo et al, 2007;Lampert et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…During the last five years, soybean crop area increased 18.3% in the state of Rio Grande do Sul, particularly in the western regions, which concentrate 45% of the beef cattle herd of that state (IBGE, 2010). Soybean crop has expanded in this new agricultural frontier in areas planted in the past with rice in the summer, which were previously used for beef production or in areas that were exclusively used for grazing (Brandão et al, 2005;Lampert et al, 2012). This will demand further intensification of beef cattle production to achieve better bioeconomic efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation